2014
DOI: 10.1016/j.acra.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Distortion in Diffusion-weighted MR Imaging of the Prostate—Contributing Factors and Strategies for Improvement

Abstract: Rationale and Objectives Image distortion on diffusion-weighted imaging (DWI) of the prostate in 3T endorectal magnetic resonance imaging (MRI) examinations is common. The aim of this study was to determine the degree of distortion on DWI using a state-of-the-art clinical protocol and to explore the main contributors to geometric distortion. Materials and Methods Forty consecutive patients underwent 3T MRI of the prostate with an endorectal coil filled with air (n = 20) or barium sulfate (n = 20). Distortion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…However, a recent study by Donato et al [8] concluded that the use of barium sulfate does not lead to significant reduction of the mean displacement in prostate DWI, underscoring the unresolved need for a robust solution to the distortion problem. We are not aware of a systematic study evaluating the effectiveness of perfluorocarbon for reducing distortions.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study by Donato et al [8] concluded that the use of barium sulfate does not lead to significant reduction of the mean displacement in prostate DWI, underscoring the unresolved need for a robust solution to the distortion problem. We are not aware of a systematic study evaluating the effectiveness of perfluorocarbon for reducing distortions.…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion imaging often increases the conspicuity of prostate cancers and detects them with greater accuracy than T2 or perfusion imaging [5,8,9]. However, standard diffusion sequences with echo planar imaging (EPI) for k-space sampling suffers from distortion artifacts due to B0 inhomogeneity [17,18]. These distortion artifacts obscure the precise location of concerning findings with this technique.…”
Section: Introductionmentioning
confidence: 99%
“…However, conventional DWI is limited in many contexts commonly encountered in the prostate, including hemorrhage, infection, and inflammation. An additional significant limitation of conventional DWI is its frequent degradation by marked spatial distortion [13]. Improvements in DWI technique may substantially improve the clinical utility of PCa imaging.…”
mentioning
confidence: 99%